Remuneration: Performance-Based Payment System in Higher Education Institutions - Andry Priharta; Nur Asni Gani; Jaharuddin Jaharuddin; Rony Edward Utama (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to solve payroll problems at Universitas Binamika Tangerang (UBT) by identifying factors that are considered to play a role in the preparation and determining the stages of the payroll system on the remuneration basis. Data collection and processing were carried out by means of focused group discussions using fishbone diagrams to obtain data related to the old payroll system and the new payroll system with the remuneration model. Discussions involving fifteen personnel as informants, documentation studies and observations were also carried out to complete data acquisition. The results of the study identified eight elements that are key to the successful preparation and implementation of a remuneration payroll system, namely type of employment, staffing level, payroll information system, layer determination, payroll element, performance indicator, system models, and implementation stage.